Automated multi-conveyor storage (AMCS) / Syahirah Saidi and Azamuddin Husin - Saidi, Syahirah; Husin, Azamuddin (2019)
In today’s fast moving, highly competitive industrial world, a manufacturing of Industrialize Building System (IBS) must be flexible, cost effective and efficient to survive. Increasing in demand for more productivity, high quality standard and better accuracy are mostly hard to achieve for mass production of precast component. In addition, current practice of material handling method and inventory control are mostly done manually and separately with more human interference. Therefore, the purpose of this study is focused on material handling management of precast component in IBS manufacturer. A detail desk study has been conducted which concentrates on the current method of material handling system, storage space utilization, inventory control management and other relevant research on various innovation approaches. Hence, Automated Multi-Conveyor Storage (AMCS) is proposed to reduce as much as possible the operator involve in construction work, cost expanses, time consuming, solving the current technical problems on material handling technology, eliminate manual and double handling works, give a high safety level of working environment as well as provide an easiest ways in material handling system. In line with this, the application AMCS is considerate the existence of current technology, working environment suitability and implementation of industry revolution 4.0 in construction.